E-Government And E-Governance: Can Its Improve Indonesian Public Service Deliveries? - Ayuning Budiati (Indonesian Association for Public Administration (IAPA), 2018)
E-government becomes strategically importance and interesting in Indonesian public service deliveries. As many Indonesian use smart phones. However, e-government and e- governance in Indonesia are still need to be improved. Meta data as the fourth stage of e- government is far way to go. Most of Indonesian e-government is still in the first stage, namely information stage. E-governance is the decisions are need to be made and implement well in e-government ‘s implementation. E-governance needs strategic thinking in processing and implement it.There is still lack of coordination in Indonesian e-governance.